IMPLEMENTASI SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SAKIP) PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN PONOROGO - Wibowo, Fendik Ari (JI@P, 2023)
Research background of this thesis is based on the result from the assesment of the Government Agencies Performance Accountability System (called: SAKIP) in Ponorogo Regency by Ministry of Administrative and Bureaucratic Reform Republic of Indonesia still getting score by â€œBBâ€ category. The gorvernment of the Ponorogo Regency has a target for the assesment of the Government Agencies Performance Accountability System in the 2020 periode will change to be A category. To achive the target must be supported by all Regional Apparatus Organitation (called: OPD) in Ponorogo regency including Departement of Public Works and Spatial Planning. It is an responsibility for all Regional Apparatus Organitation to get a score with the â€œAâ€ or â€œAAâ€ category to boost score of Government Agencies Performance Accountability System (SAKIP) in Ponorogo Regency increased form â€œBBâ€ to â€œAâ€ category. After this research was done, it was conluded that there a need some technical guidance and regulatioan related Government Agencies Performance Accountability System (SAKIP) for all the employes (ASN), as for refreshment and deeper understanding of the implementation of Government Agencies Performance Accountability System (SAKIP) with the intention they can compose Government Agencies Performance Accountability System (SAKIP) correctly. The separate office also an hamper for understanding the Government Agencies Performance Accountability System (SAKIP) well. The resources is not optimally yet, especially those who has technical background. And and there is still an inconsistency between the documents so that the perfection of the data is not good, its necessary to do some document review. The success of the implementation of the Government Agencies Performance Accountability System (SAKIP) at Departement General Work and Spatial Planning of Ponorogo regency which is measured according to Edward III's theory consists of four indicators, namely â€˜communication, resources, disposition, bureaucratic structureâ€™. Overall, the results of the research show that the ability of the employes (ASN) in the Departement General Work and Spatial Planning in responding to the policy of the Government Agency Performance Accountability System (SAKIP) is already good even though not 100% of all them understand deeply about Government Agency Performance Accountability System (SAKIP). Keywords : implementation, communication, resources, disposition, bureaucratic structure.